Does Agnosticism Exist? - D. V. Ankin (Интеллект. Инновации. Инвестиции, 2021)
The term «agnosticism» is used quite often in the philosophical literature. Usually, the meaning of this term is associated with the presence of boundaries in knowledge, and as an example of agnosticism, they refer to the philosophy of I. Kant. Nevertheless, the meaning of this term raises many questions. What are these boundaries? What exactly does Kant consider unknowable? And a number of other questions are still waiting to be answered. Our goal will be to remove some of the existing uncertainties and to demonstrate, if not senselessness, then the problematicity of the very term «agnosticism». We will try to show that what is suitable for the philosophy of religion is not always meaningful and suitable for epistemology. Our methodology will be the analysis of the logical form of statements about the existence / non-existence of something. Such statements are called existential. The methodology for studying problems through the analysis of their linguistic form is the norm for analytical philosophy. For the definition of analytic philosophy, see V. Ye. Borisov and [7]. This methodology is associated with a «linguistic turn in philosophy» [14]. In this case, the term «agnosticism» should be investigated through existential statements, through statements about the existence / non-existence of something (God, spirits, etc.). In defining the concept of agnosticism, the interpretation of the position of I. Kant in relation to the boundaries of knowledge is of great importance. The position of I. Kant is also appropriate to interpret through the ways of using existential statements. Some existential statements according to Kant turn out to be cognitively insoluble. Such are the statements about God, about spirits, about a world transcendent to our experience (things in themselves), etc. For example, it is impossible to prove or disprove the existence of God — this is not a question of cognition (epistemology), but exclusively of faith. Of particular importance is I. Kant’s division of thinking and cognition. The research carried out shows that the term «agnosticism» is often used unreasonably and even meaninglessly, especially when some a priori negative characteristic is attached to it. The use of this term turns out to be very problematic.